Rise of the New West, 1819-1829 - Turner, Frederick Jackson, 1861-1932 (Salt Lake City, UT : Project Gutenberg, 2003)
"Rise of the New West, 1819-1829" by Frederick Jackson Turner is a historical account written in the early 20th century. The book explores the transformative period in American history following the War of 1812, focusing on the social, economic, and political developments in the western United States. It delves into the significance of the westward expansion, the impact of nationalism vs. sectionalism, and how these factors contributed to the evolving identity of America during this time. At the start of the volume, Turner outlines the backdrop of late 18th and early 19th-century America, emphasizing the transition from colonial dependence to national assertiveness, marked by continued westward migration and the growth of new states. The opening chapters introduce the reader to the emergence of the "New West" as both a physical space and a culture characterized by its pioneering spirit and economic ambitions. As settlers moved westward, they faced challenges that reshaped political alliances and social dynamics, revealing tensions between various regions of the country, particularly between the established East and the expanding West. The introductory sections set the stage for deeper exploration of the complex relationships and events that defined this crucial decade in American history. (This is an automatically generated summary.)
Release date is 2003-03-01
This etext was produced by Charles Franks, George Balogh and the Online Distributed Proofreading Team
Keywords: West (U.S.) -- History; Mississippi River Valley -- History -- 1803-1865; Oregon -- History -- To 1859; United States -- Politics and government -- 1815-1861